- #1
seang
- 184
- 0
We're analyzing JK flip flop circuits and I don't understand it.
So, Given that J = x, and K = xB' , my notes say that Q+ = JQ' + K'Q. I understand that. Then, substituting, we get xA' + x'A + xB.
I have no idea how that final result was obtained. Can anyone help me with this?
So, Given that J = x, and K = xB' , my notes say that Q+ = JQ' + K'Q. I understand that. Then, substituting, we get xA' + x'A + xB.
I have no idea how that final result was obtained. Can anyone help me with this?